Stimulation Model Growth and Social Personal Development of Children Autism in Health Promotion - Atik Badi’ah; Ravik Karsidi; Ahmad Arman Subijanto; Diffah Hanim (Health Notions, 2018)
Background: Autism is a developmental disorder caused organic brain damage, difficulty communicating verbal, nonverbal. Need supervision and parental attention. The stimulation helps stimulate the brain to produce hormones in its development. Purpose: (1) analyze the internal factors, external influences growth and social personal development of autistic children (2) analyze the relationship between nutritional status and the growth and social personal development of autistic children (3) analyze the effect of stimulation of the growth and social personal development of children with autism (4) formulate a stimulation model of growth and social personal development of children with autism in health promotion. Method: This type of research is a Research and Development (R & D) research and quasi experimental method, time series design. The study was conducted in 7 autism school in Yogyakarta. The total sample of 90 children with autism. Conducted in November 2015 and April 2016. Data were analyzed using multiple linear regression, ods ratio, Mann Whitney and Wilcoxon. Results: (1) Internal factors (race) affects Weight and external factors (intranatal) and internal (genetic) influence growth and social personal development of children with autism p<0.05, (2) there is a relationship with the nutritional status of growth and social personal development of children with autism p <0.05, (3) There is a stimulation effect on the growth and development of social personal development of children with autism with p <0.05, (4) the drafting of a stimulation model of growth and social personal development of children with autism. Conclusion: Establishment of stimulation model of growth and social personal development of children autism in the form of manual stimulation of growth and social personal development of children with autism in health promotion.Keywords: Stimulation model, Growth, Social personal development, Autism, Health promotion